2018
DOI: 10.6018/ijes/2018/1/258971
|View full text |Cite
|
Sign up to set email alerts
|

Study of accuracy and grammatical complexity in EFL writing

Abstract: The present study seeks to compare the writing products of EFL undergraduates using as measures accuracy and grammatical complexity. It also intends to describe the evolution of the morphological and syntactic errors as English is used by learners. A total of 100 learners of English as a foreign language participated in the study. They were divided into two groups according to their Oxford Placement Test score: group A was formed by 36 advanced students; and group B was made up of 64 upper intermediate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Lexico-grammatical errors are common in these people's writing and prevent them from producing good-quality compositions (Luo & Liao, 2015). Many studies have investigated the linguistic errors made by EFL learners and have found that, when writing, EFL learners make both grammatical and lexical errors (Chaudhary & Al Zahrani, 2020;Karazoun, 2016;Lahuerta, 2018;Nuruzzaman et al, 2018;Sermsook et al, 2017;Zülal, 2020).…”
Section: Grammatical and Lexical Accuracy In Efl Learners' Writingmentioning
confidence: 99%
“…Lexico-grammatical errors are common in these people's writing and prevent them from producing good-quality compositions (Luo & Liao, 2015). Many studies have investigated the linguistic errors made by EFL learners and have found that, when writing, EFL learners make both grammatical and lexical errors (Chaudhary & Al Zahrani, 2020;Karazoun, 2016;Lahuerta, 2018;Nuruzzaman et al, 2018;Sermsook et al, 2017;Zülal, 2020).…”
Section: Grammatical and Lexical Accuracy In Efl Learners' Writingmentioning
confidence: 99%
“…In addition, some pronunciation differences between Spanish varieties (like /θ/ and /s/ phonemes) may have not been considered in previous studies. To our knowledge, in this country only Lahuerta (2015Lahuerta ( , 2018 has assessed the type of errors that students in Spain produce when spelling in English. Nevertheless, these studies focused on other aspects, like fluency or grammatical and lexical complexity, spelling remained in the background.…”
Section: Our Studymentioning
confidence: 99%
“…Writing skill is a subset of students' language competence, with an emphasis on writing abilities. Students are demanded to produce various genres and rhetorical features and include language-specific abilities such as vocabulary and syntactic structures (Lahuerta, 2018;Baroudy, 2008). In EFL contexts, writing is considered the most difficult language skill to be mastered.…”
Section: Introductionmentioning
confidence: 99%